Brassinosteroid and Hydrogen Peroxide Interdependently Induce Stomatal Opening by Promoting Guard Cell Starch Degradation. Issue 4 (12th February 2020) - Li, Jin-Ge; Fan, Min; Hua, Wenbo; Tian, Yanchen; Chen, Lian-Ge; Sun, Yu; Bai, Ming-Yi
Abstract : Starch degradation in guard cells is induced by the phytohormone brassinosteroid and the redox signal hydrogen peroxide to promote stomatal opening. Abstract: Starch is the major storage carbohydrate in plants and functions in buffering carbon and energy availability for plant fitness with challenging environmental conditions. The timing and extent of starch degradation appear to be determined by diverse hormonal and environmental signals; however, our understanding of the regulation of starch metabolism is fragmentary. Here, we demonstrate that the phytohormone brassinosteroid (BR) and redox signal hydrogen peroxide (H2 O2 ) induce the breakdown of starch in guard cells, which promotes stomatal opening. The BR-insensitive mutant bri1-116 accumulated high levels of starch in guard cells, impairing stomatal opening in response to light. The gain-of-function mutant bzr1-1D suppressed the starch excess phenotype of bri1-116, thereby promoting stomatal opening. BRASSINAZOLE-RESISTANT1 (BZR1) interacts with the basic leucine zipper transcription factor G-BOX BINDING FACTOR2 (GBF2) to promote the expression of β-AMYLASE1 ( BAM1 ), which is responsible for starch degradation in guard cells. H2 O2 induces BZR1 oxidation, enhancing the interaction between BZR1 and GBF2 to increase BAM1 transcription. Mutations in BAM1 lead to starch accumulation and reduce the effects of BR and H2 O2 on stomatal opening. Overall, this study uncovers the critical roles of BR and H2 O2 in regulating guard cell starch metabolism and stomatal opening.